Measurement of Principal Modes in Few-Mode Fibers by S2 Method - Zixiang Di (IEEE Photonics Journal, 2020)
Using principal modes (PMs) can avoid the inter-mode crosstalk in fiber-optic communication and reduce the complexity of digital signal processing. In this paper, a new detection method for PMs based on spatially and spectrally resolved imaging (S2) is used to recover their intensity distributions and inter-mode dispersion parameters. This method collects the optical interference information on a two-dimensional plane at different frequencies. The collected data can be used to characterize the principal modes, including their patterns and differential mode group delays. Due to the frequency invariance of PMs even in mode coupling state, which is studied carefully, this proposed method is shown to be robust. Analyses based on a four-mode fiber show that the distributed fluctuation of the coupling coefficients break the frequency invariance of PMs. We experimentally measure the mode characteristics of a four-mode fiber with S2 method. The results show that the mode group delays of degenerate modes can be separated in mode coupling state, which is exactly appropriate for the modified measurement method.